LEGISLATIVE AND ADMINISTRATIVE REGULATIONS IN TURKEY WITHIN THE FRAMEWORK OF KYOTO PROTOCOL - Torlak, S. Evinç; Kulaç, Onur; Çeliktürk, Tanzer; Arslan, Recep (European Scientific Journal, ESJ, 2015)
Kyoto Protocol which is the last phase of the idea of a need for an international corporation in order to prevent ecocide since 1970s was put into operation in 2005. Kyoto Protocol is an addition of “United Nations Framework Convention on Climate Change (UNFCCC)” which was accepted in Rio Summit. In this study first of all, the development process of Kyoto Protocol before its operation will be analyzed, the classification according to the responsibilities and development of the state parties will be dealt. Later on, what kind of solutions does the protocol bring to the climate change problem and the mechanisms that are applied for the projected declines for the emission rates will be scrutinized. Lastly, the legislative and administrative steps that have been taken in the frame of Kyoto Protocol that is effective in Turkey since 2009, and the deficiencies during the adaption process of the protocol is aimed to be put forth.